Anxiety And Short Distance Running Performance In Female Athletes - Ikina Rizki Kahiji; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Indonesian Journal of Physical Education and Sport Science)
Studi purpose. There are many cases in athletics where performance declines, especially in women, due to excessive anxiety. Often, they think this is a normal thing, but this can have fatal consequences and interfere with the performance of female athletes in short-distance running events. Thus, this study aims to examine the relationship between anxiety and short-distance running performance in female athletes.